Social Inclusion-Based Community Learning Program at Dinas Kearsipan dan Perpustakaan (Diarpus) of Sukabumi District - Muhammad Ilyasa Sastrawijaya; Fahma Rianti (Librarianship in Muslim Societies, 2022)
Social inclusion-based library transformation is an approach to library services committed to improving the library user community’s quality of life and welfare. Since 2014, Dinas Kearsipan dan Perpustakaan of Sukabumi district (Diarpus of Sukabumi district) has started implementing community learning programs. This study aims to identify the impact felt by the community related to welfare after participating in various social inclusion-based community learning programs implemented by the Diarpus of  Sukabumi district. This study uses a qualitative method with a phenomenological approach. Informants in this study were librarians, participants, and teachers of community learning programs. This research reveals that the community learning program implemented by Diarpus of Sukabumi district has helped the community develop its potential. It can be seen from several results; able to do business online through the Bukalapak application, produce Herbal Care Library as an herbal product, increase foreign language skills in English and Japanese, and increase public insight through writing classes in the library. The community also uses the library as a learning center and becomes more familiar with the library, and makes the library a vehicle for lifelong learning. Community learning programs need to reach out to the people of Sukabumi district more broadly, add a variety of activities, collaborate with more parties, and involve the community in program development.Social Inclusion-Based Community Learning Program at Dinas Kearsipan dan Perpustakaan (Diarpus) of Sukabumi